Brain Death and Organ Transplantation in Judicial Case Due to Child Abuse - Feyza İnceköy Girgin; Emel Uyar; Makbule Nilüfer Yalındağ Öztürk (Galenos Yayinevi, 2019)
Child abuse is a social and medical problem that causes serious morbidly and mortality in children, is very common in our country. The role of the pediatrician is enormous in suspicion of child abuse and inhibition of the process which can be mortal. Brain death children can be organ donors with the permission of their families. In potential donors who are victims of child abuse various problems concerning forensic medicine, judicial needs and ethics are confronted. Here we present a 10 month old boy with severe abusive head trauma who was diagnosed with brain death on 56nd hour during his stay in our pediatric intensive care unit. 4 hours after the brain death determination, his family consented to organ donation. The medical examiner's office gave a timely response and released the body for organ donation. Within 38 hours of the diagnosis, the patient became a donor for kidney, liver and cornea transplantation. With this case we wanted to emphasize the importance of the awareness in early diagnosis of child abuse, along with early recognition of brain death for organ transplantation. In addition, we pointed out that medical examiners cases due to child abuse could be potential donors as well.